THE COMPRESSIVE STRENGTH OF LIGNOSULPHONATE-STABILIZED EXTRUDED-EARTH MASONRY UNITS - Maskell, Daniel; Walker, Peter; Heath, Andrew (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
Earthen (unired-clay) bricks offer several distinct advantages over conventional ired-clay bricks and other high-energy masonry units. Most notably, there is signiicantly lower-environmental impact, including carbon emissions during manufacture, than comparable products, with unired-clay bricks having an estimated 14% of the energy of ired bricks, and 25% of concrete blocks. Earthen construction is able to provide passive-environmental controls, including the regulation of temperature and humidity, which can be utilized in unired-clay masonry to improve internal levels of comfort. The commercialization of unired-clay masonry as a structural material is dependent on several factors. Modern earthenconstruction methods need to it in with demands of contemporary construction, compete commercially and provide a highquality consistent performance. To ensure that thin-walled unired-clay masonry can be used in a load-bearing application, it is important to consider the effect high-moisture content, due to accidental and intentional wetting, has on the strength of the material, as well as the building unit. This paper presents initial indings from an investigation into the development of low-impact alternative stabilizers. Cement and lime are widely used in some countries, but both have an associated embodied energy and carbon emissions that may hinder the beneits of unired clay as a mainstream building material. The use of lignosulphonate was chosen as a way of minimizing the adverse environmental impacts while improving water resilience, an essential requirement for thin-walled load-bearing masonry using earth. Unconined-compressive strength of extruded-soil samples, which were stabilized with three types of lignosulphonate, were tested both dry and wet as a basis for comparing loss of str ength due to exposure to a wet envi ronment.